Rock Blasting Terms and Symbols : a Dictionary of Symbols and Terms in Rock Blasting and Related Areas like Drilling, Mining and Rock Mechanics /: a Dictionary of Symbols and Terms in Rock Blasting and Related Areas like Drilling, Mining and Rock Mechanics. (1998) - Unknown
No abstract available